Analysis of The Potential Bankruptcy of Beginning Entrepreneurs Using The Altman Z-Score, SpringateOhlson, Grover, and Zmijewski Methods In The Middle Of The Covid-19 Pandemic - Isnaini, Teuku; Yusnidar, Cut; Boihaki, Boihaki (LPPM Universitas PGRI Sumatera Barat, 2024)
This study uses the Altman Z Score, Springate, Ohlson, Grover, and Zmijewski methods to measure the potential for bankruptcy for Aceh beginner entrepreneurs registered with the Cooperatives, Small and Medium Enterprises Office in 2022. The purpose of this study is to analyse and test whether there are differences in the calculation results between Altman, Springate, Ohlson, Grover, and Zmijewski methods when used to predict the bankruptcy of business actors in 2022, as well as the most accurate method in predicting the bankruptcy of businesses registered as SMEs in 2022. The population used in this study is all Aceh beginner entrepreneurs registered in the Department of Cooperatives, SMEs in 2022, selected with certain criteria using the objective sampling method. The data in this study is quantitative data with survey data sources, namely secondary from the Annual Financial Reports published by the Cooperatives and SMEs Office in 2022. The data acquisition technique uses documentation techniques. The data analysis method used descriptive statistical methods, normality tests, and hypothesis testing using a paired sample t-test to test the accuracy of the method. The data analysis method used descriptive statistical techniques, normality tests, hypothesis testing with paired sample t-test and accuracy of prediction methods. The results obtained showed that there were significant differences between the methods of Altman, Springate, Ohlson, Grover, and Zmijewski, and there were methods with the highest level of accuracy, namely the Grover model of 90.17%.